1974
DOI: 10.1007/bf01219535
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes of carbohydrate and fat metabolism in anti-insulin serum diabetes; inactivation by free fatty acids and the protective effect of cellular protein

Abstract: The possibility that free fatty acids (FFA) and their CoN esters may directly inhibit the activity of enzymes of glycolysis and lipogenesis was studied in liver and adipose tissue of acutely diabetic rats. Despite a marked elevation in tissue FFA, the activity of glucose-6phosphate dehydrogenase, phospbofructokinase, pyruvate kinase, u-glycerophosphate dehydrogenase, aldolase, citrate synthetase, and several other enzymes was not affected 3 or 6 h after anti-insulin serum injection. The activities of hepatic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1976
1976
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…An earlier study demonstrated that the LCACE-mediated inhibitory effect decreased with increasing homogenate concentration, suggesting that unphysiologically high LCACE concentrations would be required to exert a physiologically relevant inhibition (47). Although total LCACE concentrations in tissues may range from 5 to 160 M, free LCACE concentration has been estimated to be Ͻ200 nM, although the actual free LCACE concentration for any tissue is not known (9).…”
Section: Discussionmentioning
confidence: 98%
“…An earlier study demonstrated that the LCACE-mediated inhibitory effect decreased with increasing homogenate concentration, suggesting that unphysiologically high LCACE concentrations would be required to exert a physiologically relevant inhibition (47). Although total LCACE concentrations in tissues may range from 5 to 160 M, free LCACE concentration has been estimated to be Ͻ200 nM, although the actual free LCACE concentration for any tissue is not known (9).…”
Section: Discussionmentioning
confidence: 98%
“…Evidence from in vivo or liver perfusion studies indicates that there is not a sufficient variation in tissue concentrations of ATP, ADP, or AMP to bring about significant alterations in the two enzyme activities (Clark et al, 1974;Tarnowski and Seemann, 1967;Exton and Park, 1969;Burch et al, 1970;Hems et al, 1966). Under conditions that stimulate gluconeogenesis (starvation, glucagon administration, and diabetes), the known rise in the concentration of 3-P-glycerate (Exton and Park, 1969) and possibly free fatty acids (Shafrir and Ruderman, 1974) would favor increased FDPase activity and, in the presence of the high intracellular levels of ATP (>3 µ /g wet weight), decreased PFK activity. Refeeding or a lowered glucagon level would result in a drop in 3-P-glycerate concentrations that would allow inactivation of FDPase by ATP and increased activity of PFK.…”
Section: Discussionmentioning
confidence: 99%